Penggunaan Sumber Belajar Diktat Buatan Guru Pada Pembelajaran Seni Budaya Di MTS Padang Laweh Kabupaten Sijunjung - Driyanda Litaimer; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2019)
This article aimed to explain the results of learning the art of music by using a course book made by teacher on Cultural Arts (Music) subject at MTs Padang Laweh, Sijunjung Regency. The main instrument in this study was the researcher himself and assisted with supporting instruments such as stationeries and cameras. The technique of data collecting was done by survey, literature study, observation and interviews. Then, the data were analyzed by looking at the results of observation and the results of interviews that had been conducted during the study. The results of the study indicated that interpersonal communication applied all learning methods, through the course book of cultural arts learning made by art and culture teacher at MTs Padang Laweh in Sijunjung District succeeded in the learning process through the course book. The learning process was designed in such a way as to apply the concept of simple and fun learning process to produce young generation that are intelligent, active and characterized. The implementation of the course book objectives consisted of interpersonal communication which referred to the continuity of education in which all activities involved teacher and students. Interpersonal communication was proven to be effective in helping teacher and students in the learning process because they could understand and each other’s characters. Thus, the educational process could take place well and effectively. The achievements of the MTs Padang Laweh in Sijunjung Regency indicate the success of teaching materials of the course book applied at the school.